Unveiling the threat of beech leaf disease: lessons from North America - Kantor, Camelia; Demirel, Melik C.; Kantor, Mihail (Frontiers in Forests and Global Change, 2025)
Beech Leaf Disease (BLD), caused by the foliar nematode Litylenchus crenatae, has emerged as a swiftly spreading forest disease across North America. This previously unknown nematode and the disease it causes have been devastating for North American beech forests, posing serious threats to biodiversity and ecosystem stability. The rapid spread of BLD and other recent forest pests serves as cautionary examples, illustrating how quickly a pathogen can establish itself in new non-native regions, leading to significant ecological and economic consequences. The destruction brought by this nematode in just a decade highlights the potentially disastrous effects of BLD if it spreads to other vital beech forest areas, particularly in European countries and China, where beech trees are essential for industries and markets that depend on such hardwood species. The loss of beech forests could compel industries to depend more on alternative raw materials that are significantly less sustainable and environmentally friendly, leading to supply chain instability and major price fluctuations. Urgent actions, such as implementing quarantine regulations for the BLD nematode, international research collaboration in areas such as breeding BLD-resistant beech trees, developing economically feasible large-scale tree treatments, and enhancing BLD screening through Artificial Intelligence—driven image—based diagnosis tools and geospatial surveillance approaches, are essential to prevent BLD from escalating into a global forest crisis.